Proposed new interior design for Naza Bikers Dream Club and services, at Jalan Ampang of Jalan Jelatek, 55100 Kuala Lumpur. / Maznul Khusni Kamal Jamil - Kamal Jamil, Maznul Khusni (Faculty of Architecture, Planning and Surveying, 2010)
A final year student pursuing a diploma course in Interior Design is required to prepare a final year project. The design of the project should be related closely to current issues or similar to it. The knowledge and skill acquired during the duration of the course should be practise and onto the drawing. This also includes the research, case study, interviewing of clients, designing proposals, preparing art work, preparing presentation drawings, design development and last but not least the final presentation. The proposed project is Naza Bikers Dream'. The idea to undertake this project was given from issues was Naza Bikers Dream Club had been re-structured . Thereafter, a plan was proposed to prepare a premise design that may interest and fulfil the aspiration of the proprietor of the premise, owners and customers of the legendary vehicle. From the research and observation conducted on the product and the premise, the information and details gathered was used as a guideline to prepare the design. After scouting for a while, an empty building structure in Ampang Road was chosen as a proposed site for this project. The objective was to design and prepare a “Naza Bikers Dream” club and service with the concept and style best suited to the Naza Bikers Dream Sdn, Bhd image. It is sincerely hoped that the proposed design would give the premise the desired image projection that need to enhanced the interest of the proprietor, Naza Bikers Dream' member club and also enthusiasts.